Myths and Realities of Informal Public Transport in Developing Countries : Approaches for Improving the Sector - Discussion Paper - Kumar, Ajay (Washington, DC: World Bank, 2022)
It is often said that transport is the one economic sector that can degrade as incomes increase. The degradation is manifested in increasing congestion, pollution, accidents, and other traffic related maladies. One view is that the root of the problem lies in rising incomes that lead to even faster-rising motorization. Another assessment sees a motorization-induced decline of “formal” publictransport systems and the rise of “informal” services as key issues, but it is unclear whether the rise of the informal sector is the result of transport system degradation or the cause. Understanding the basic causes of the transport system’s decline and the dominance of informal public transport is essential before improvements can be identified. Because of its social, economic, and environmental importance, the paper’s main focus is on public transport in general, specifically its so-called “informal” aspects. The objectives of thepaper are to: a) examine the uniqueness of public transport systems in Sub-Saharan African cities in terms of their historical, institutional, spatial, social, environmental, economic, and political contexts; b) explore the causes of the decline of developing country transport systems in general and in public transport’s degradation in particular; c) discuss commonly-held misconceptions sothat policymakers at all levels of government can understand the issues that must be addressed if “informal” public transport is to be improved as part of an enhanced, customer-driven public transport system; and d) propose the outline of a roadmap for making improvements. Subsequent work will examine in more detail what an improved public transport system would look like and how it can be achieved. This paper also focuses on all aspects of so-called “minibus-taxis,” the oldest and most prevalent informal sector mode in Africa, Latin America, and Asia. This mode goes by different names in different places; however, the many causes of its rise and the impacts of the rise are common throughout the developing world. Relatively new informal public transport operations using three-wheeled shared ride vehicles (e.g., “Tempos” in India) and motorcycle taxis (e.g., “Xiom” in Vietnam) have arisen as minibus taxis with similar operating and business models.